Lymphocyte-Predominant Hodgkin’s Disease in Children: A Case Study and Review of the Literature - James R. Stier; Robert J. Vasquez (Case Reports in Oncological Medicine)
A three-year-old boy presented with an enlarging neck mass. Biopsy demonstrated IgD-positive nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL), which was staged as IIa. The patient received cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) with rituximab and had excellent results. NLPHL is a relatively rare disease that is biologically distinct from classic Hodgkin lymphoma (cHL). NLPHL is a B-cell malignancy likely of germinal center origin that has an overall good prognosis and favorable response to treatment. Unlike cHL, NLPHL is ubiquitously CD20-positive. Recent evidence supports the efficacy of targeted anti-CD20 therapy in NLPHL, though prospective data is limited. This case demonstrates several unique features of NLPHL and further supports the use of rituximab in front-line therapy. The clinical characteristics among patients at various ages are discussed with a special focus on the IgD-positive subtype. A thorough literature search demonstrates this to be the youngest patient with NLPHL yet described.